Biology of Glyphepomis dubia Campos & Souza, 2016 (Hemiptera: Pentatomidae) and the parasitoids Telenomus podisi Ashmead, 1893 and Trissolcus basalis (Wollaston, 1858) (Hymenoptera: Platygastridae) on rice. - SOUZA, J. R. (2021)
he life cycle of stink bug, Glyphepomis dubia and the development of two egg parasitoids (Telenomus podisi and Trissolcus basalis) were studied at the Federal University of Maranhão, at 26 ± 2oC, relative humidity (RH) of 60 ± 10% and 12h photophase. Individuals used in the study were collected from seven rice fields located around the municipality of Arari, Maranhão, Brazil, and maintained in greenhouse and laboratory for the life cycle studies. From egg to adult, G. dubia took 35.2 days to complete the life cycle. The oviposition period was 37 days, with egg masses of about 12 eggs each and viability of 93.1%. Longevity was 53 and 65 days for females and males, respectively. The egg parasitoids Te. podisi and Tr. basalis parasitized and developed in G. dubia eggs; however, the biological characteristics of Tr. basalis were affected. Emergence of the parasitoids was higher for Te. podisi (83.5%) compared to the records for Tr. basalis (50.4%). Therefore, G. dubia may potentially achieve a pest status and Te. podisi is a promising biological control agent for G. dubia management in Brazil due to its higher longevity and better reproductive parameters.